Propuesta de un sistema de gestión de inventario para la cadena de suministro de una planta envasadora de GLP mediante la metodología Lean Supply Chain - Quiñones Álvarez, Rodrigo Isacc (2024)
Every supply chain seeks to enhance its processes through optimization. Our research, titled “Proposal for an Inventory Management System for the Supply Chain in a GLP Bottling and Distribution Plant through Lean Supply Chain” implements this methodology to reduce inventory losses and efficiently manage the production and dispatch processes. The study aims to demonstrate that utilizing this method will increase logistical operations efficiency, improve competitiveness, and enhance inventory control and management related to operational processes from acquisition to distribution. Ultimately, this approach helps save costs, boost business efficiency, and improve the level of service provided. To achieve this goal, initial research was gathered to demonstrate the reduction of waste and increased efficiency in the supply chain using Lean Supply Chain principles. This research supports the evaluation and development of a new system that integrates the execution of Lean Manufacturing pillars with the processes across the entire supply chain. Subsequently, the qualitative and quantitative effects are summarized, and the effectiveness of the system is assessed in terms of continuous improvement and process control, frequency of events encountered by the chain, productivity, and profitability. The present study could be useful and applicable to the distribution and sale of hydrocarbons sector in Peru or related facilities.